Effects of Proteins and Mineral Ions on the Physicochemical Properties of 1,3-Dioleoyl-2-Palmitoylglycerol Emulsion to Mimic a Liquid Infant Formula - Wang, Qi; Xu, Yuxi; Liu, Yanchen; Qian, Fang; Mu, Guangqing; Zhu, Xuemei (Frontiers in Nutrition, 2022)
The proteins and minerals in infant formula not only play a role of nutrients but also have an important effect on the physical and chemical stability of emulsions. In this study, calcium carbonate (0 or 9.08 mM) and potassium chloride (0 or 15.96 mM) as representatives of divalent and monovalent minerals were added into 1,3-dioleoyl-2-palmitoylglycerol (OPO) emulsions containing with different ratios (10:0, 9:1, 6:4, 5:5, 0:10) of whey protein isolate (WPI) and sodium caseinate (CN). The influence of proteins and minerals on emulsion stability was investigated by analyzing particle size, zeta potential, creaming index, rheological properties, storage stability and lipid oxidation. The OPO emulsion could be destabilized by adding Ca2+ as shown from the increased particle size index, creaming index and the decreased magnitude of zeta potential. Divalent ions could affect the electrostatic interactions between lipid droplets and the interactive effects of ion surface adsorption. In addition, the effect of different protein ratios on the physical stability of the emulsion was not significant under the same ionic type conditions. In term of the chemical stability, higher oxidized values were found in emulsions stabled by CN alone than those containing WPI. Our study showed that the protein ratios and the minerals played important roles in the stability of the OPO emulsion, which may provide a reference for the development and utilization of liquid infant formula.